Conflict partners and infrastructure use in safety critical events in cycling – Results from a naturalistic cycling study. (May 2015) - Schleinitz, Katja; Petzoldt, Tibor; Franke-Bartholdt, Luise; Krems, Josef F.; Gehlert, Tina
Highlights: Behavioural data of cyclists was recorded by means of a naturalistic cycling study. Safety relevant events were identified and analysed. Around 60% of the events did not involve motorised vehicles. Only around 35% of the events occurred on the road. A sole research focus on on-road, bicycle–motor vehicle conflicts seems unjustified. Abstract: Accident statistics show that cyclists are at considerable risk of being involved in a crash. However, statistics based on police reports are often heavily biased towards on-road, bicycle–motor vehicle crashes. Crashes that do not involve motorised vehicles or that occur on other types of infrastructure are neglected. Naturalistic cycling methodology appears to be a promising approach to address these issues. The goal of this study was to identify and classify safety critical cycling events involving a variety of conflict partners and covering all types of infrastructure. Thirty-one participants in three age groups had their own bicycles equipped with a data acquisition system. Participants rode their modified bike as usual for a period of four weeks. Over 1600 trips were recorded overall. We were able to identify 77 safety critical events during the observation period. Only 43% of these events involved motorised vehicles as conflict partners. Conflicts with other cyclists and pedestrians accounted for about 57% of the situations. Likewise, less than 35% of the events occurred on-road. The data show that although motorised vehicles are still the single biggest threat to cycling safety, and roads still constitute one of the most crash prone types of infrastructure, the importance of crashes that do not involve motorised road users or occur not on-road should not be underestimated.